COMPREHENSIVE REVIEW OF THE IMPACT OF NURSE STAFFING RATIOS ON PATIENT SAFETY AND OUTCOMES. - Fatima Nasser Ibrahim Asiri, Hanan Mofareh Ahmed Asiri, Mofareh Hassan Mohammed Al Muhmal, Nada Nasser Lbrahim Asiri, Noora Nasser Lbrahim Asiri, Tahani Ahmed Mohammed Assiri, Ohood Mohammed Yahya Abutaleb Zayed Ali Zayed Al Atwah (Chelonian Research Foundation, 2022)
The ratio of nurses in the staff is crucial for the safety and outcomes of patients in health care institutions. The extensive review is investigates the correlation between the nurse staffing ratios on the one hand and the safety of patients and the mortality rate on the other hand, hospital-acquired infections, medication errors, and patient satisfaction. The deterioration or recovery of specific outcomes results from many factors. This paper examines the literature and gives evidence for the causal connection between nurse staffing ratios and patient outcomes. The essay touches on the topics of nurse staffing ratio determinants and possible approaches to the staffing planning of an optimal amount. The review describes the significance of nurse staffing levels and articulates guidelines for developing hospital care policymakers and boards of directors. Keywords: Nurse staffing ratios, Patient safety, Patient outcomes, Healthcare quality, Nursing workforce.